Contemporary Fiqh Review on the Sale of Sacrificial Animals that Have Not Reached Sufficient Age from the Perspectives of Islamic Economic Law and Positive Law - Akbar, Muhamad Iqbal; Wagianto, Wagianto; Zaki, Muhammad (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
The practice of selling sacrificial animals (qurban) that have not reached the minimum legal or religious age required for qurban remains widespread in Indonesian society. This phenomenon often raises both practical and jurisprudential dilemmas, especially in the months leading up to Eid al-Adha. Many qurban committees and buyers choose animals that appear large and healthy but are in fact below the required age. This article examines the legal validity of such practices through three analytical lenses: contemporary Islamic jurisprudence (fiqh mu‘?shir), Islamic economic law, and Indonesian positive law. Using a normative-juridical method with a qualitative-descriptive approach, this study explores classical and contemporary fiqh texts, official fatwas from bodies such as MUI and Dar al-Ifta’ Egypt, and relevant Indonesian laws including consumer protection regulations. The findings reveal that although the majority of classical scholars maintain strict requirements regarding animal age, contemporary scholars introduce a more purposive approach, prioritizing animal quality and the maq??id al-shar?‘ah over rigid literalism. In Islamic economic law, transparency and mutual consent remain core principles for valid transactions, especially concerning goods intended for religious rituals. Under Indonesian positive law, a qurban transaction remains valid as long as all terms are agreed upon by the parties and the buyer is not misled. The study concludes with policy recommendations for Islamic legal institutions, local governments, and livestock sellers to provide better guidance and protections for Muslim consumers in fulfilling their religious obligations.